2011
DOI: 10.1590/s0102-09352011000600010
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation markers in the transplanted canine transmissible venereal tumor

Abstract: Adult male mongrel dogs were subcutaneously transplanted with the canine transmissible venereal tumor (TVT) on the hypogastric region. Twelve specimens of tumors were collected, half during the proliferative phase and the other half during the regressive phase. Fragments of the tumor were fixed in 10% buffered formalin and routinely processed for light microscopy. Sections of 4µm were stained by Schorr or AgNOR or either immunostained for MIB1 (Ki67). Schorr stain, AgNOR and MIB1 showed an increased proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The number and area of NORs represent parameters that reflect the level of proliferative activity of cells (Santos et al 2011). Santos et al (2011, in a study on canine transmissible venereal tumor (TVT), demonstrated that the greater the number of small NORs, the greater the proliferative activity of cells, with tumors in the growth phase but this was not observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The number and area of NORs represent parameters that reflect the level of proliferative activity of cells (Santos et al 2011). Santos et al (2011, in a study on canine transmissible venereal tumor (TVT), demonstrated that the greater the number of small NORs, the greater the proliferative activity of cells, with tumors in the growth phase but this was not observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Ki-67 PI is related to tumor progression, metastatic ability, and prognostic value (30, 31, 36). It was higher in the pre-treated samples than the post-treated samples.…”
Section: Discussionmentioning
confidence: 99%
“…All slides were immunostained with polymer-based, non-avidin-biotin EnVision detection system TM (Dako, Denmark), and 3, 3′-diaminobenzidine tetrahydrochloride (DAB) substrate (Dako, Denmark) as a visualization system. The Ki-67 PI was defined as the percentage of nuclear immunolabeling positive cells (at least 1,000 cells were counted) among the total number of tumor cells counted in at least 10 HPF (36).…”
Section: Methodsmentioning
confidence: 99%
“…The number of AgNOR is related to the cell cycle and proliferative activity of the cell 33 . The quantification of AgNOR area is related to the tumor growth rate, cell proliferative activity and consequently tumor progression 34 , 35 . Thus, we used AgNOR quantification to evaluate the antitumor effect of EEOb in vivo .…”
Section: Resultsmentioning
confidence: 99%